Effects of the combination of Er:YAG laser and sandblasting on the shear bond strength between zirconia and resin cement - Urias Silva Vasconcelos; Thalisson Saymo de Oliveira Silva; Daylana Pacheco da Silva; Graciela Maria Oliveira Sipaúba; Valdimar da Silva Valente; Raquel Virginia Zanetti; Carmem Dolores Vilarinho Soares de Moura (Universidade Estadual de Campinas, 2019)
Aim: This study was conducted to determine the bond strength between zirconia ceramic and resin luting cement according to the type of surface treatment applied. Methods: Sixty zirconia cylinders measuring 4 x 4 mm were manufactured and distributed into five experimental groups and a control group (n = 10): G1 - sandblasting with 110 μm aluminum oxide; G2 - sandblasting with 30 μm Rocatec Soft®; G3 - Er:YAG laser irradiation at 400 mJ; G4 - Er:YAG laser combined with sandblasting with aluminum oxide; G5 - Er:YAG laser combined with sandblasting with Rocatec Soft®; G6 - no treatment (Control). The zirconia cylinders were bonded in the center of composite resin cylinders (6 mm diameter) using RelyX Ultimate® cement. Shear strength was measured after thermocycling (6000 cycles and 5-55° C). Data were analyzed using one-way ANOVA and Tukey's post-hoc with a 5% significance level. Results: Group 4 had a significantly higher shear strength than all the other groups, except Group 1. Group 3 had a significantly lower shear strength compared with Groups 1 and 4. Conclusion: Sandblasting with 110μm aluminum oxide particles after laser irradiation may be an effective zirconia surface treatment. The use of Er: YAG laser alone is not effective at increasing the bond between resin cement and zirconia.